Maternal Surgery During Pregnancy Has a Transient Adverse Effect on the Developing Fetal Rabbit Brain. Issue 3 (September 2020) - Van der Veeken, L.; Van der Merwe, J.; Devroe, S.; Inversetti, A.; Galgano, A.; Bleeser, T.; Meeusen, R.; Rex, S.; Deprest, J.
Abstract : ( Am J Obstet Gynecol . 2019;221:355.e1–355.e19) Approximately 0.2% to 2% of pregnant women in the United States and Europe undergo nonobstetric surgery each year. These procedures are often performed under general anesthesia (GA). Clinicians, researchers, and organizations have expressed concern about the potential adverse effects of anesthesia on the developing brain of an infant or fetus. Previous clinical research studies have indicated varying conclusions, but there is a general consensus that the developing brain is most vulnerable when the brain is at peak growth, beginning mid-gestation, and continues after delivery. While earlier animal studies have explored the effects of neonatal anesthesia only, little research has explored the effects of GA administered for surgery, as well as the effect of surgery itself during pregnancy. This study investigated whether the combination of maternal anesthesia and surgery, using a rabbit model, would lead to poorer neurological outcomes at birth, as well as behavioral and cognitive debilitation in the time after delivery.